The Use Of Total Physical Response Method For Improving The Speaking Skills/ استخدام طريقة الاستجابة الجسدية الكاملة لترقية مهارة الكلام - Nasution, Sahkholid; Suti’ah, Wirda (Ijaz Arabi Journal of Arabic Learning, 2023)
A common problem in learning Arabic is students' weak ability to speak Arabic, even though they have studied Arabic for a long time. This encourages Arabic language teachers to be smart in choosing and using the right methods. One of the methods in question is the Total Physical Response Method, abbreviated as TPR. This research aims to determine the improvement in students' speaking skills using the Total Physical Response method. This research uses the Classroom Action Research method. Interviews, observation, documentation, and tests carried out data collection. The total population is 27 class VII students at MTs Raudhatul Akmal Batang Kuis. The research results show that students' abilities increase by using the Total Physical Response method, this can be seen from the students' activeness in participating in learning and the Post-test scores are higher than the Pre-test scores. In the pre-cycle only 26.0% of students exceeded the Minimum Completeness Criteria (MCC), in the first cycle, 70.4% of Arabic language teachers, both in schools, madrasas, and Islamic boarding schools, applied the Total Physical Response method so that students' ability to speak the language Arabic is getting better. Students who reached the MCC, and in cycle II 92.6% of students reached the MCC. This shows that the Total Physical Response method is effective in improving students' ability to speak Arabic. The implications of the research provide alternatives to Arabic language teachers, both in schools, madrasas, and Islamic boarding schools, to apply the Total Physical Response method so that students' ability to speak Arabic is getting better.